Its Prohibitive Cost: The Bicycle, the New Woman and Conspicuous Display. (2nd January 2017) - Chen, Eva
ABSTRACT: As a Victorian form of transport, the bicycle is often linked with the New Woman and hailed as a harbinger of emancipation and public mobility for women, or a tool for female sartorial reform and physical improvement. This paper argues that until the end of the nineteenth century, the bicycle, with its high cost and its association with the younger members of the upper-middle class, is also a tool of conspicuous consumption and fashionable display. As a crucial accessory of the much advertised, ridiculed but also emulated ensemble that constitutes the New Woman, the bicycle signifies her complicity with modern commodity culture, which, though entailing more opportunities and greater emancipation along gender lines for many bourgeois women, at the same time functions as a new marker of visible class privilege denying access to other less privileged women. This paper locates the bicycle, in its initial stage of the mid-1890s bicycle craze, as an integral part of a wider late Victorian material culture of conspicuous consumption and phantasmagoria where commodities, objects and spectacles increasingly articulate or fashion human subjectivities and denote their classed identities.